Removal of oil from synthetic heavy crude oil-in-water emulsions by the association of glass raschig rings and ultrasound. Issue 1 (22nd December 2021) - Ronchi, Renata Peterle; Negris, Luana; Melo, Breno Nonato; Pereira, Letícia S. F.; Vicente, Maristela A.; Flores, Erico M. M.; Santos, Maria de Fátima Pereira
Abstract: As a byproduct of the crude oil industry, oily water is a major environmental concern. In this study, a novel methodology that used low-frequency ultrasound (US) for the removal of oil from the production of oily water was proposed. A continuous phase was prepared by dissolving NaCl (18 g·L −1 ), CaCl2 (6 g·L −1 ), and MgCl2 (3 g·L −1 ) in water. Synthetic oil-in-water emulsion was without adding artificial emulsifiers (oil contents: 495–687 mg·dm −3 ) with median droplet size distributions of approximately 10 µm was prepared using a Brazilian heavy crude oil (API gravity of 11.9). Experiments were performed using ultrasonic baths operating at 35, 45, and 130 kHz at 60 °C in the presence of glass Raschig rings without any addition of chemical demulsifiers. Other materials were also evaluated: PVC; PTFE; Polypropylene; steel; and copper. For the synthetic oil-in-water emulsion with 495 mg·dm −3 oil, in the presence of glass Raschig rings, an oil removal efficiency of approximately 76.4% (35 kHz, 20 min) was achieved. Higher removal efficiencies were obtained for synthetic oil-in-water with 495 mg·dm −3 oil than for those with 687 mg·dm −3 oil (50.1%, 130 kHz, 20 min). Although typically used for emulsification, these findings reveal that low-frequency US association of glass Raschig rings is also a promising technology for treating the produced water to remove oil. Graphical Abstract: UF0001